Influence Of Palm Oil Fuel Ash (Pofa) Towards The Performance Of Kernelrazzo Concrete - Owolabi, Olanrewaju Sharafadeen Babatunde (2023)
This research examined the mix proportion and strength between partially replaced palm kernel shell (PKS) with marble chippings and cement wherein the granite content of the kernelrazzo concrete was replaced by 0%, 10%, 20%, 30%, 40% and 50% of palm kernel shell and 100%, 90%, 80%, 70%, 60% and 50% of marble chippings for stage one, respectively.